Total thyroidectomy versus subtotal thyroidectomy in treatment of multinodular goiter: a meta-analysis - Ahmed A. Kamel; Mohamed Kamel (The Egyptian Journal of Otolaryngology, 2024)
Abstract Background The surgical management of multinodular goiter is the treatment of choice for the majority of cases. There is controversy between radical resection with the lifelong thyroxine substitution and function-preserving resection with the risk for recurrence, and the complications associated with total thyroidectomy. Objective The aim of the present study was to compare the outcome of total thyroidectomy (TT) in comparison with subtotal thyroidectomy (ST) as regards hypocalcemia, transient nerve injury, and recurrence rate. Patients and methods This study included published English medical articles in the last 20 years, concerning the treatment of multinodular goiter. Results Meta-analysis was for the evaluation of surgical outcomes after surgical management of multinodular goiter including total thyroidectomy versus subtotal thyroidectomy by comparing the TT versus ST in our study including 23 studies included of the total number of patients (4485) who underwent subtotal thyroidectomy versus the total number of patients (7116) who underwent total thyroidectomy; a comparison was done as regards postoperative complications including RLN injury (transient or permanent), rate of recurrence, need for reoperation, and incidence of postoperative hypocalcemia. The incidence of RLN injury is lower in ST compared to TT, and its recurrence is much lower in TT than in ST. Conclusion This meta-analysis showed that the advantages of total thyroidectomy include adequate eradication of the disease, prevention of recurrent goiter, and avoidance of the need for completion surgery in case of occult malignancy, but it is associated with higher morbidity (postoperative thyroidectomy complications: RLN palsy and hypoparathyroidism) and the need for lifelong replacement therapy (L-thyroxin supplementation).